EFEK WAKTU TAHAN SINTERING DAN KOMPOSISI BAHAN TERHADAP KEKERASAN DAN STRUKTUR MAKRO PRODUK METALURGI SERBUK (Energy, Materials and Product Design, 2022)
The development of science and technology today is very rapid and develop in various sectors, that one is in engineering material sector, specifically composite material . One method of composite formation is powder metallurgy method. Powder metallurgy is a metalworking technology in which components are manufactured from metal powders. This study aims to determine the effect of holding time sintering and mixing composition on hardness and macro structure observations. The material used in this study was aluminum waste that came from the rest of the window cutting. The specimens were made using powder metallurgy method. In this study the variations used were the sintering holding time of 120 minutes, 180 minutes, 240 minutes, composition variations of 80% Al : 17% Sic : 3% Glass, 80% Al : 14% Sic : 6% Glass, 80% Al : 11 % Sic : 9% Glass, 80% Al : 8% Sic : 12% Glass. Some control variables are grain size 100 mesh, mixing 15 minutes, compacting 7 tons and sintering temperature 600oC. The results obtained are the highest hardness value is found in the specimen with a sintering temperature of 600oC with a sintering holding time of 240 minutes at a material composition of 80:17:03 which is 90.33 HRF. The macro structure observations showed that there was a smaller porosity in the specimens with high hardness values. The results of the overall mechanical properties test show that the variation of the sintering resistance time has an effect on the specimen which will give time for the formation of stronger bonds between particles. While the variation in the composition of the material with SiC reinforcement the more the percentage given, the greater the composite hardness.